Teenage Motherhood and Sibling Outcomes - Heissel, Jennifer A. (American Economic Review, 2017)
Using annual longitudinal data, I show that all children in families with teen childbearing are on a downward trajectory several years before pregnancy begins. Compared to students on similar trajectories from families without teenage childbearing, siblings of teen mothers have lower test scores, higher high school dropout, and higher juvenile justice system exposure following the birth. The change in test score outcomes occurs after the baby is born, indicating that the child's arrival affects performance, rather than some unobserved occurrence leading to both teen pregnancy and poor outcomes. The test scores for teen mothers drop in the year of pregnancy.